Metastatic colon cancer from extrahepatic cholangiocarcinoma presenting as painless jaundice: case report and literature review - Vabi, Benjamin W.; Carter, Jeffrey; Rong, Rong; Wang, Minhua; Corasanti, James G.; Gibbs, John F. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Background: Cholangiocarcinoma (CCA) is a rare cancer of the biliary epithelium comprising only about 3% of all gastrointestinal malignancies. It is a highly aggressive malignancy and confers a dismal prognosis with majority of patients presenting with metastatic disease. Metastatic CCA to the colon is extremely rare with only few cases reported in the literature. Case presentation: We present a 61-year-old patient with incidental synchronous metastatic colonic adenocarcinoma from extra-hepatic CCA. Laboratory data revealed significant indirect hyperbilirubinemia and transaminitis. Imaging study showed intrahepatic bile ducts prominence without mass lesions. Incidentally, there was diffuse colonic thickening without mass lesions or obstruction. Endoscopic retrograde cholangiopancreatography (ERCP) showed a common bile duct stricture. Brushings were consistent with CCA. Screening colonoscopy identified nodularity and biopsy and immunostaining were consistent with CCA metastasis to colon. The patient elected for palliative and comfort care. Conclusions: Metastatic CCA to the colon is a rare pattern of distant spread that may pose a diagnostic challenge. Some salient characteristics may assist in the differentiation of primary colon cancer and metastatic colon cancer from CCA. Little remains known about the pathogenic behavior of metastatic secondary colorectal cancer. And more so, the management approach to such metastatic cancer still remains to be defined. Screening colonoscopy in patients presenting with resectable CCA may alter management. Furthermore, whether patients with history of resected CCA may benefit from a more frequent screening colonoscopy remains to be validated.